The effect of ultrasound duty cycle in biodiesel production from Ceiba pentandra - Iderisa F.; Silitonga A.S.; Kusumo F.; Shamsuddina A.H.; Nomanbhaya S.M.; Sebayang A.H.; Sutrisno J.; Bela N. (IOP Publishing Ltd, 2023)
Fourier transform infrared spectroscopy; Potassium hydroxide; Sustainable development; Transesterification; Ultrasonics; Biodiesel production; Duty-cycle; Energy usage; FTIR spectroscopy; Optimum conditions; Physio-chemical properties; Pulse modes; Transesterification reaction; Biodiesel